EVALUATION OF THE RELATIONSHIP BETWEEN TAX POTENTIAL AND TAX BURDEN - V. K. Girayev (Финансы: теория и практика, 2017)
Russian Economy under crisis conditions features deepening disparities in development of territories, intensified and aggravated budgetary problems which are arising, inter alia, due to improper methodology for assessment of tax potential in conjunction with tax burden. The paper suggests the author’s technique designed to assess tax potential on the basis of such factors of production as invested capital and salary amount ensuring reproductive needs of citizens.The suggested method was tested using Russia’s economic data: it revealed an uneven distribution of tax burden and provided estimation of its distribution in terms of production factors, Based on the economically defined tax potential, the paper shows the necessity of reforming the Russian tax system through reducing the tax burden on enterprises. The author shows that the tax potential should be determined taking into account the relationships between consumed and created elements as well as establishes the relationship between the portion of society aggregated income which is re-distributed through consumption funds and the portion of national income. The conclusions may be used in defining the tax reform strategy, in planning tax revenues and improvement of inter-budgetary relations.